Seriously Implementing Health Capacity Strengthening Programs in Africa; Comment on "Implementation of a Health Management Mentoring Program: Year-1 Evaluation of Its Impact on Health System Strengthening in Zambézia Province, Mozambique" - Luis Velez Lapão (Kerman University of Medical Sciences, 2015)
Faced with the challenges of healthcare reform, skills and new capabilities are needed to support the reform and it is of crucial importance in Africa where shortages affects the health system resilience. Edwards et al provides a good example of the challenge of implementing a mentoring program in one province in a sub-Saharan country. From this example, various aspects of strengthening the capacity of managers in healthcare are examined based on our experience in action-training in Africa, as mentoring shares many characteristics with action-training. What practical lessons can be drawn to promote the strengthening so that managers can better intervene in complex contexts? Deeper involvement of health authorities and more rigorous approaches are seriously desirable for the proper development of health capacity strengthening programs in Africa.